2022
DOI: 10.3389/fcvm.2022.876465
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mortality Outcomes in Acute Myocardial Infarction Patients With or Without Standard Modifiable Cardiovascular Risk Factors

Abstract: BackgroundAcute myocardial infarction (AMI) cases have decreased in part due to the advent of targeted therapies for standard modifiable cardiovascular disease risk factors (SMuRF). Recent studies have reported that ST-elevation myocardial infarction (STEMI) patients without SMuRF (termed “SMuRF-less”) may be increasing in prevalence and have worse outcomes than “SMuRF-positive” patients. As these studies have been limited to STEMI and comprised mainly Caucasian cohorts, we investigated the changes in the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 53 publications
2
25
1
Order By: Relevance
“…The reported outcomes of SMuRF-less patients are conflicting. A study of 3081 STEMI patients by Vernon et al found SMuRF-less patients had a higher mortality compared to SMuRF patients, in agreement with other studies of STEMI patients [3,5,16,18]. Similarly, our analysis shows SMuRF-less patients presenting with T2AMI had increased risk of mortality, MACCE and stroke.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The reported outcomes of SMuRF-less patients are conflicting. A study of 3081 STEMI patients by Vernon et al found SMuRF-less patients had a higher mortality compared to SMuRF patients, in agreement with other studies of STEMI patients [3,5,16,18]. Similarly, our analysis shows SMuRF-less patients presenting with T2AMI had increased risk of mortality, MACCE and stroke.…”
Section: Discussionsupporting
confidence: 92%
“…We report several important findings. Firstly, the proportion of SMuRF-less patients presenting with T2AMI (7.6%) is lower than has been reported in T1AMI studies (14-27% for STEMI and 3.7% to 23% for NSTEMI) [2,3,5,15,16]. Secondly, SMuRF-less patients were more likely to be younger, white, and female with fewer comorbidities than SMuRF patients.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Previous studies have demonstrated that multiple risk factors and their interactions are associated with the long-term prognosis of patients with STEMI treated with primary PCI ( 7 , 8 ). Patients with STEMI who are stratified into subgroups according to these risk factors have distinct clinical profiles, resulting in different MACEs risks ( 9 11 ). Therefore, additional subgroup-specific evaluation to predict the long-term prognosis of patients following STEMI is required to achieve effective management in different patient subgroups.…”
Section: Introductionmentioning
confidence: 99%